Model of smoothing roughness on GaAs wafer surface by using nonabrasive chemical-and-mechanical polishing - Fomin, A.V.; Pashchenko, G.A.; Kravetskyi, M.Yu.; Lutsyshyn, I.G. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2017)
Studied experimentally in this work has been the process of smoothing relief roughness on the GaAs wafer surface by using the method of contactless nonabrasive chemical-and-mechanical polishing under conditions of its rotational movement relatively to the polishing plate. The model of this process has been developed under the assumption that the pure diffusion smoothing mechanism takes place there. It has been shown that satisfactory correspondence between respective calculated dependences and experimental results can be reached by introducing the “effective” diffusion coefficient, providing an account of etchant convection.